It is Time to Auction Slots at Congested Airports - Martin Bichler; Peter Cramton; Peter Gritzmann; Axel Ockenfels (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Airport time slots are currently awarded by historic use, with only small number reserved for new entrants. This hampers competition, promotes inefficient slot utilisation, and contributes to congestion. This column revisits the idea of carefully auctioning time slots at congested airports in order to foster competition by more flexibly allocating slots, as opposed to the current use-it-or-lose-it approach which favours the status quo.
Keywords: 330